A Systematic Literature Review of Gender and Politics: Stereotypes of Gender in Political Zone on Social Media - Al Fauzi Rahmat; Galih Bagas Soesilo; Andy Arya Maulana Wijaya; Nareewan Klinrat (MUWAZAH : jurnal kajian gender, 2022)
Gender stereotypes in political discourse, particularly on social media, have intensified and become pivotal in shaping public perceptions and political engagement. Despite extensive scholarly efforts to examine gender and politics within online platforms, there remains a critical gap in systematically mapping the thematic and conceptual patterns across studies. This research aims to identify dominant trends, recurring stereotypes, and thematic clusters in gender-political discourses on social media. Adopting a qualitative systematic literature review approach, the study analyzes 89 peer-reviewed articles from the Scopus database (2012–2021), with a focus on the social sciences. Data analysis was conducted using NVivo 12 Plus and VOSViewer to generate thematic classifications, density visualizations, and project maps. Key findings reveal an increasing prevalence of topics such as gender and sexuality, female leadership, anti-immigration narratives, and the politicization of identities, including Black, Muslim, and White women. These themes intersect with broader political narratives and reflect persistent digital gender biases. The study identifies three central conceptual propositions—gender, politics, and social media—as mutually reinforcing spheres of discourse. This review not only fills a critical scholarly gap but also contributes to the epistemological understanding of gendered political communication, offering foundational insights for future interdisciplinary inquiry and policy-oriented research.